How and Why to Regulate False Political Advertising in Australia - Hill, Lisa. author. aut Link
XIII, 170 p. 4 illus., 1 illus. in color.
Keywords: This book represents the first comprehensive, Australia-focused treatment of the problem of false election information disseminated for the purpose of gaining an electoral advantage. It explores cautious legal regulation as the most effective and decisive approach to the issue. In doing so, the book demonstrates that, although experiments with such remedies have met with mixed success elsewhere, they are nevertheless viable, especially in Australia where they have strong public support and are able to withstand constitutional challenge. This is an open access book. Lisa Hill is a Professor of Politics at the University of Adelaide. Her research interests are in electoral studies, political theory and history of ideas. Max Douglass is a teaching and research assistant at the University of Adelaide, and a Juris Doctor candidate at the University of Melbourne Law School. Ravi Baltutis is a research assistant at the University of Adelaide, a former Student Editor of the Adelaide Law Review and currently employed at Dentons, a global law firm.